Situation Analysis of Awareness of Assistive Technology of Teachers for Children with Special Needs in Punjab - Muhammad Javed Aftab, Shaheen Pasha, Navid Ur Rehman (JIE, 2023)
The primary goal of this research was to examine the current state of knowledge regarding assistive technology among Punjab educators who work with students who have special needs. The population of the study was honorable teachers of the department of special education Punjab. The questionnaire was established as a tool to record the opinions of the special education teaching staff against the required information. The population sample participated and provided their valuable opinions were 100 teaching staff from all over Punjab. Awareness of teachers towards assistive technology is in appropriated because assistive technology is very expensive and not easily accessible. Due to the unawareness of the teachers about the usage of available assistive technology, our institutions are unable to operate these technologies in daily base studies of children. Assistive technology is very necessary and helpful for a person with a disability. They speed up the working ability of the person and create a proper and easy environment. Key recommendations made by the researchers are aware of assistive technology should be increased and also aware the students about the significance of assistive technology (AT) in the lives of special needs students.